Cell therapy for stroke: use of local astrocytes - Chouchane, Melek; Costa, Marcos R. (Frontiers in Cellular Neuroscience, 2012)
Stroke refers to a variety of conditions caused by the occlusion or hemorrhage of blood vessels supplying the brain, which is one of the main causes of death and the leading cause of disability worldwide. In the last years, cell-based therapies have been proposed as a new approach to ameliorate post stroke deficits. However, the most appropriate type of cell to be used in such therapies, as well as their sources, remains a matter of intense research. A good candidate cell should, in principle, display high plasticity to generate diverse types of neurons and, at the same type, low risk to cause undesired outcomes, such as malignant transformation. Recently, a new approach grounded on the reprogramming of endogenous astrocytes towards neuronal fates emerged as an alternative to restore neurological functions in several central nervous system diseases. In this perspective, we review data about the potential of astrocytes to become functional neurons following expression of neurogenic genes and discuss the potential benefits and risks of reprogramming astrocytes in the glial scar to replace neurons lost after stroke.